Studi Kasus Tentang Perilaku Suka Mencari Perhatian di Kelas pada Siswa Kelas V SD Negeri Sraten 01 Gatak, Sukoharjo Tahun Ajaran 2015/2016 - Fitrianto, Robert Mahendra; , Drs. Saring Marsudi, SH. M.Pd (2016)
This study aim is to know: (1) the indicator of the student's behaviour which like to looking for attention in the fifth grade of SDN Sraten 01 Gatak, (2) the factor which causes of the student's behaviour which like to looking for attention in the fifth grade of SDN Sraten 01 Gatak, (3) the result of the student's behaviour which like to looking for attention in the fifth grade of SDN Sraten 01 Gatak. The methods of arranging of this data in this thesis are observation, interview, and documentation. Based on this research concluded that: (1) the indicator of the student's behaviour which like to looking for attention in the fifth grade of SDN Sraten 01 Gatak; that is: the student always ask something which it is not necessary question (the question out off the material), arrogant with his friend, like to looking for attention from his friend, and having the dominant talk in the teaching learning process, (2) the factor caused of the student's behaviour which like to looking for attention in the fifth grade of SDN Sraten 01 Gatak, that is: there is no attention from his friend, no respect from his friend, not a famous child in the class, and there is no friend who need him to be friend, (3) the result of this student's behaviour which like to lookung for attention in the fifth grade of SDN Sraten 01 Gatak: that is: is the student feels to difficult in the teaching and learning process, feel to difficult to adaptation with his friend, and be excommunicated friend.